MYC promotes immune-suppression in triple-negative breast cancer via inhibition of interferon signaling - Zimmerli, Dario; Brambillasca, Chiara S.; Talens, Francien; Bhin, Jinhyuk; Linstra, Renske; Romanens, Lou; Bhattacharya, Arkajyoti; Joosten, Stacey E. P.; Da Silva, Ana Moises; Padrao, Nuno; Wellenstein, Max D.; Kersten, Kelly; et al. (Nature communications, 2022)
The limited efficacy of immune checkpoint inhibitor treatment in triple-negative breast cancer (TNBC) patients is attributed to sparse or unresponsive tumor-infiltrating lymphocytes, but the mechanisms that lead to a therapy resistant tumor immune microenvironment are incompletely known. Here we show a strong correlation between MYC expression and loss of immune signatures in human TNBC. In mouse models of TNBC proficient or deficient of breast cancer type 1 susceptibility gene (BRCA1), MYC overexpression dramatically decreases lymphocyte infiltration in tumors, along with immune signature remodelling. MYC-mediated suppression of inflammatory signalling induced by BRCA1/2 inactivation is confirmed in human TNBC cell lines. Moreover, MYC overexpression prevents the recruitment and activation of lymphocytes in both human and mouse TNBC co-culture models. Chromatin-immunoprecipitation-sequencing reveals that MYC, together with its co-repressor MIZ1, directly binds promoters of multiple interferon-signalling genes, resulting in their downregulation. MYC overexpression thus counters tumor growth inhibition by a Stimulator of Interferon Genes (STING) agonist via suppressing induction of interferon signalling. Together, our data reveal that MYC suppresses innate immunity and facilitates tumor immune escape, explaining the poor immunogenicity of MYC-overexpressing TNBCs. Tripe-negative breast cancers poorly respond to immune checkpoint inhibition therapy, due to their immune-hostile tumour microenvironment. Authors here show that the oncogene MYC plays a pivotal role in suppressing anti-tumour immunity via directly regulating the transcription of interferon signalling genes.